Causal role of immune cell phenotypes in idiopathic sudden sensorineural hearing loss: a bi-directional Mendelian randomization study - Li, Wanqing; Zhou, Qiang; Zhou, Linsa; Cao, Longhe; Zhu, Chuansai; Dai, Zhijian; Lin, Sen (Frontiers in Neurology, 2024)
Background A growing body of evidence suggests that immunological processes have a significant role in developing idiopathic sudden sensorineural hearing loss (SSHL). However, few studies have examined the association between immune cell phenotype and SSHL using Mendelian Randomization (MR). Methods The online genome-wide association studies (GWAS) database was used to compile data from GWAS covering 731 immunophenotypes and SSHL. Inverse variance weighted (IVW) analysis was primarily used for MR study, and single nucleotide polymorphisms (SNPs) associated with immunophenotypes served as dependent variables. A sensitivity study and the false discovery rate (FDR) correction were used to examine the MR hypothesis. In addition, the possibility of reverse causality between immunophenotype and SSHL was validated by reverse MR. Reverse MR was analyzed in a manner consistent with forward MR. Results After FDR correction and sensitivity analysis, we screened 7 immunophenotypes, including IgD+ CD38dim %lymphocyte (95% CI: 1.0019, 1.0742, p = 3.87 × 10−2, FDR = 1.15 × 10−2); Unsw mem AC (95% CI: 1.004, 1.2522, p = 4.23 × 10−2, FDR = 2.25 × 10−2); CD86+ myeloid DC AC (95% CI: 1.0083, 1.1147, p = 2.24 × 10−2, FDR = 4.27 × 10−2); CD33dim HLA DR− AC (95% CI: 1.0046, 1.0583, p = 2.12 × 10−2, FDR = 4.69 × 10−2); SSC-A on CD8br (95% CI: 1.0028, 1.1461, p = 4.12 × 10−2, FDR = 4.71 × 10−2); CD45RA− CD4+ %T cell (95% CI: 1.0036, 1.0503, p = 2.32 × 10−2, FDR = 4.82 × 10−2); DP (CD4+CD8+) AC (95% CI: 1.011, 1.2091, p = 2.78 × 10−2, FDR = 4.97 × 10−2). There was a strong causal relationship with SSHL onset, and the reliability of the results was verified. Furthermore, the immunological cell profile and SSHL did not appear to be closely associated, as shown by reverse MR analysis. Conclusion Our study provides more support for the current hypothesis that immunophenotypes and the pathophysiology of SSHL are closely associated. Further validation is needed to assess the role of these immunophenotypes in SSHL.